Breastfeeding knowledge and profile of pregnant women: a cross-sectional study in Primary Health Care - Brum, Vanessa dos Santos; Oliveira, Isabelle Amorim de; Rodrigues , Jonas de Almeida (Brazilian Dental Science, 2026)
Objective: To describe the profile, knowledge, and prior experiences related to breastfeeding among pregnant women in a southern Brazilian city. Material and Methods: This cross-sectional study included 106 pregnant women aged 16–45 years attending dental prenatal consultations at three public healthcare units. Data were collected between September 2021 and November 2024 using a standardized questionnaire with 19 closed-ended questions on sociodemographic characteristics, breastfeeding knowledge, previous experiences, and intentions. Descriptive analyses and Chi-square tests were performed. Results: Participants were mostly adult women with completed secondary education and family income above two minimum wages. While 98.1% intended to breastfeed, only 13.3% reported receiving professional guidance. Although 54.7% correctly identified the ideal duration of exclusive breastfeeding, 33.1% believed other liquids should be offered during this period. Knowledge about breastfeeding’s impact on breathing and oral development was limited. Intentions to offer pacifiers (55.7%) and bottles (44.3%) were frequent. No significant associations were observed between professional guidance and the evaluated variables. Conclusion: Pregnant women showed strong intentions to breastfeed, but knowledge gaps remain and professional counseling is limited. These findings highlight the need to strengthen breastfeeding promotion during prenatal care, reinforcing the role of dentists in multidisciplinary healthcare teams.KEYWORDSBreast feeding; Health knowledge, attitudes, practice; Pregnant women; Prenatal care; Primary Health Care.